Optimizing Artificial Intelligence Systems for Real-World Applications - Boya Marqas , Ridwan; Saman M. Almufty; ENGİN AVCI, Prof. Dr. and R. Asaad, Renas (International Journal of Scientific World, 2025)
The optimization of Artificial Intelligence (AI) systems is critical for improving performance, scalability, and adaptability across various real-world applications. This paper explores key optimization techniques, including algorithmic enhancements, hardware acceleration, software tools, and data preprocessing. Challenges such as resource constraints, domain-specific requirements, and ethical concerns are analyzed. Case studies in healthcare, finance, manufacturing, and autonomous systems demonstrate notable improvements in accuracy, efficiency, and scalability. A systematic framework is proposed to guide AI optimization, incorporating iterative testing, hardware-software integration, and deployment strategies. The findings highlight AI optimization’s transformative potential in developing scalable, efficient, and ethical systems. Future research directions include the creation of generalizable frameworks, energy-efficient AI, and fairness-aware optimization to ensure broader applicability and equity.